The Prevalence and Clinical Features of Skin Irritation Caused by Infection Prevention Measures During COVID-19 in the Mecca Region, Saudi Arabia - ZahrAllayali A; Al-Doboke A; Alosaimy R; Alabbasi R; Alharbi S; Fageeh S; Altayyar S; Azher R (Dove Medical Press, 2021)
Ahmed ZahrAllayali,1 Amal Al-Doboke,2 Rawan Alosaimy,2 Renan Alabbasi,2 Sara Alharbi,2 Sarah Fageeh,2 Shahad Altayyar,2 Ruqayya Azher3 1Dermatology, Department of Internal Medicine, College of Medicine, Umm Al-Qura University, Al-Abdia Main Campus, Makkah, Saudi Arabia; 2College of Medicine, Umm Al-Qura University, Al-Abdia Main Campus, Makkah, Saudi Arabia; 3Department of Community Medicine, College of Medicine, Umm Al-Qura University, Al-Abdia Main Campus, Makkah, Saudi ArabiaCorrespondence: Ahmed ZahrAllayaliDermatology, Department of Internal Medicine, College of Medicine, Umm Al-Qura University, Al-Abdia Main Campus, P.O Box 715, Makkah, Saudi ArabiaTel +966590041029Email ahmedz98@hotmail.comPurpose: Due to the COVID-19 pandemic, recommendations to prevent infection suggest increasing the frequency of handwashing and disinfection; however, these measures can have negative implications on our skin. This study aims to evaluate whether these measures correlate with new-onset skin damage or can exacerbate hand eczema among the general population.Materials and Methods: This was a descriptive, cross-sectional, survey-based study, including the general population of Mecca region, Saudi Arabia. To achieve the study's aim, an online questionnaire to the general population comprising 25 items was distributed via social media apps during the pandemic between October 23 and November 21, 2020. Data were automatically collected in Excel and entered into SPSS for analysis.Results: A total of 783 participants were included in this study, of whom 695 (88.8%) were female. A history of hand eczema was reported among 123 (15.7%) participants, and 270 (34.5%) had a history of atopy. During the COVID-19 pandemic, 86 (13.0%) participants noticed new-onset skin irritation, while 81 (31.3%) of the participants reported exacerbation of earlier hand allergic dermatitis. The most frequent symptoms were dryness and feeling of tightness. Additionally, most participants among both groups noticed that skin lesions appeared for less than 10 days. The frequent handwashing statistically increased following the onset of the pandemic (p=0.001), there is association between new-onset symptoms and more frequent handwashing, as well as the use of hand disinfectants, during the pandemic (p=0.001).Conclusion: Our study suggests that the general population's skin was negatively affected by COVID-19 precautions, particularly those with a history of hand eczema. We recommend spreading awareness of skin protective modalities and the use of new infection prevention measures, such as regular skin moisturization for hand protection and possibly using less damaging skin disinfectants like ozonized water provided it is scientifically proven effective in disinfecting COVID-19 virus.Keywords: COVID-19 pandemic, precautions, questionnaire, general population, skin, hand eczema